Autotrophic nitrogen removal and potential microbial interactions in anammox systems with different ammonia and organic carbon concentrations. (October 2020) - Zhang, Tianqi; Wei, Nan; Wu, Guangxue
Graphical abstract: Highlights: Stable operation of anammox systems was achieved under different conditions. Candidatus Kuenenia, Nitrospira and Thauera were functional microorganisms. Metabolisms of nitrogen and carbon were achieved by microbial cooperation. Microbial interactions were affected by concentrations of ammonia and acetate. Amino acid cross-feeding and AHLs-based communication always existed. Abstract: Anaerobic ammonium oxidation (anammox) is a key process to achieve autotrophic nitrogen removal from wastewater. Four continuous flow biological reactors were operated by feeding different concentrations of ammonia and with or without the addition of acetate. The best nitrogen removal was achieved at the condition of high ammonia concentration without organic carbon, with obtained the nitrogen removal loading rate of 2.2 g N/(L·d) and the nitrogen removal percentage of 92%. Candidatus Kuenenia was the dominant genus and was stimulated at a high ammonia concentration, while a high acetate concentration enhanced the denitrifying activity. Ca. Kuenenia, Nitrospira, Thauera and other microorganisms constituted the microbial network responsible for both nitrogen and carbon metabolisms. Ca. Kuenenia lacked synthetases of alanine, aspartate and methionine, which could be supplied by nitrifiers and denitrifiers. This cross-feeding strategy was conducive to efficient biosynthesis and degradation of amino acids. N-decanoyl homoserine lactone was detected in both biomass and extracellular polymeric substances phases. Acyl-homoserine lactones (AHLs) based quorum sensing and quorum quenching microorganisms coexisted in anammox systems, playing important roles in biosynthesis, sensing and quenching of AHLs.